2011
DOI: 10.1039/c0nr00497a
|View full text |Cite
|
Sign up to set email alerts
|

Core-shell Fe3O4@SiO2nanoparticles synthesized with well-dispersed hydrophilic Fe3O4seeds

Abstract: Silica coated magnetite (Fe3O4@SiO2) core-shell nanoparticles (NPs) with controlled silica shell thicknesses were prepared by a modified Stöber method using 20 nm hydrophilic Fe3O4 NPs as seeds. The core-shell NPs were characterized by X-ray diffraction (XRD), transmission electron microscopy (TEM), high-resolution TEM (HRTEM), selected area electron diffraction (SAED), and UV-Vis adsorption spectra (UV-Vis). The results imply that NPs consist of a crystalline magnetite core and an amorphous silica shell. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
135
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 307 publications
(148 citation statements)
references
References 50 publications
12
135
0
1
Order By: Relevance
“…Further, the intensity of the silicon (Si) peak was increased sharply as observed from the EDS analysis ( Figure 7c). We also studied the influence of Fe 3 O 4 nanocubes concentration on the coating process and found that the concentration of the Fe 3 O 4 does not affect the thickness of the silica shell, and this result was in agreement with the earlier report [4].…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…Further, the intensity of the silicon (Si) peak was increased sharply as observed from the EDS analysis ( Figure 7c). We also studied the influence of Fe 3 O 4 nanocubes concentration on the coating process and found that the concentration of the Fe 3 O 4 does not affect the thickness of the silica shell, and this result was in agreement with the earlier report [4].…”
Section: Resultssupporting
confidence: 81%
“…However in their study, they coated the noble metal with silica and not magnetic materials. Hence the coating process involves mainly two reaction of nucleation (hydrolysis) and growth (condensation), and the silica tends to predominantly coat onto the magnetic nanoparticles as the growth rate is much higher than nucleation rate [4], one must be very careful of reaction parameters optimization. Based on the reported method, it was found that lower temperature, lower pH value, lower TEOS concentration, and less H 2 O are predominant in facilitating the condensation process and consequently the coating process [18][19][20].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The size of the Fe 3 O 4 @a-SiO2 particle was about ~25 nm and the thickness is ~9 nm. Thus, the Fe 3 O 4 /a-SiO 2 nanocomposites have successfully formed a Fe 3 O 4 @a-SiO 2 core shell [14,18]. There were significant different shape and size of the composite particles of Fe 3 O 4 @ a-SiO 2 amorphous (#sample 1) and Fe 3 O 4 @ c-SiO2 (crystal), as shown in Figure 2 (a) and Figure 2 (b); composite particle size of Fe3O4/a-SiO 2 was greater than the particle size of the Fe 3 O 4 @c-SiO 2 composite.…”
Section: Data Of Ftir Characterization Of Fe 3 O 4 /A-sio 2 Compositesmentioning
confidence: 99%
“…The MNPs and MNPs/silica nanoparticles were synthesized according to previous report [3]. Then 1 mL of chloropropyltrimethoxysilane was dissolved in toluene.…”
Section: General Procedures For Preparation Of Modified Mnps and Pur Nmentioning
confidence: 99%